Fiscalidad imperial y desarrollo regional en el siglo XVIII. El monopolio del tabaco como instrumento de fomento en la Luisiana - Náter, Laura (El Colegio de México, A.C., 2004)
This paper analyzes Spain's Eighteenth-century tobacco policies in Louisiana, where it created a fiscal institution for mainly political reasons, subordinating economical yields and revenues to the  region's political  and  strategic needs.  This  case contrasts with the management  and exploitation of the same institution in other  Spanish colonial  properties,  which  also held monopolies of different products, including tobacco.  This study  shows that the tobacco monopoly was during the Eighteenth-century one of the Real Hacienda's favorite fiscal instruments for increasing revenues with which to promote economic development in certain colonies. The author's main conclusions refer to the mechanisms  through which the Real Hacienda de la Nueva  España used tobacco revenues to strengthen the economy of Louisiana.